Reproductive Performance and Factors Influencing Fetal Outcome: A Practical Guide to Experiments on Lung Development in A Nitro Fen-Induced Rat Model for Congenital Diaphragmatic Hernia - Beck Veronika; Deckx Sebastiaan; Sandaite Inga; Deprest Thomas; Depres Jan (International Journal of Ethology, 2018)
Our study aims to help researchers calculate resources based on a rat breeding colony for experiments on fetal lung development. The Wistar rat is commonly used in experimental research. In the context of fetal lung studies, the nitrofen rat is a model for pulmonary hypoplasia and congenital diaphragmatic hernia. Data needed to calculate resources for new experiments are not easily available. We prospectively acquired data on the reproductive performance and fetal outcome of 314 consecutive virgin Wistar dams in our fetal lung research breeding colony. We define the impact of breeding conditions on rat fertility and evaluate different methods to diagnose early rat gestation. Effects of nitrofen exposure as well as fetal surgery in terms of prenatal mortality and gross anatomical parameters of lung development are quantified in nitrofen-exposed and -unexposed fetuses from embryonic day 19 to 21 in 12h intervals. A reduced mating interval (1h) provides a great degree of experimental control with feasible pregnancy rates and a large litter size. Nitrofen exposure, as well as fetal surgery, depict high fetal survival rates. Fetal lung findings were very reproducible and could allow for reduction of animals utilized within experimental groups.
Keywords: Breeding colony